Trusting the wisdom of stranger and eWOM credibility in collaborative consumption: a conceptual paper/ Siti Azira Babh ... [et al.] - Babh, Siti Azira; Ismail, Mohd Noor Ismawi; Abdul Aziz, Azdel; Razli, Izyanti Awang (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
Using Airbnb as a platform for collaborative consumption, this conceptual paper helps us extend our understanding on the relationship between the benefits and satisfaction that Airbnb guests achieved during their stay and their intention to spread positive eWOM among Malaysians. Numerous studies have suggested significant impacts of eWOM on their businesses, specifically accommodation products in the tourism industry, how,ever scares study on it in the Airbnb Malaysia setting. This study will be using quantitative data through a survey method and a structured survey questionnaire that will be distributed to 400 respondents who have stayed at least once in any Airbnb accommodation located in Malaysia. Descriptive data will be analysed using SPSS and PLS-SEM will be employed to examine the relationship of the benefits of collaborative consumption towards customer satisfaction and eWOM. In addition, the role of customer satisfaction in the relationship between collaborative consumption benefits a and eWOM will be analyzed. The findings of this study will contribute toward a further understanding of how consumer decision-making can be affected by a myriad of factors, including the words of total strangers. This study will also add to the existing literature on Airbnb by understanding the mechanics behind what drives consumers to be satisfied with the offerings of Airbnb and what factors perceived to be more important than others.